19 Ablation of isolated ventricular arrhythmias from the left ventricular apex in patients without ischemic heart disease. (October 2018) - Walsh, K; Supple, G; Garcia, F; Callans, D; Zado, E; Lin, D; Marchlinski, F
Abstract : Introduction: The left ventricular apex (LVA) is an uncommon isolated source of ventricular arrhythmias (VA), in patients without coronary artery disease (CAD).We aimed to characterize the incidence, clinical and ECG features of this type of VA in a tertiary referral ablation center. Methods: We retrospectively reviewed the medical records of ablation cases from 1999 to 2016 at our center. We identified VA cases and then identified those with isolated VA from LVA in the absence of CAD. We recorded patient demographics, clinical features and ECG morphology for each of these cases. Results: 2779 VA ablations were performed between 1999 and 2016. 20 (0.7%) of these were performed for isolated LVA VA in the absence of CAD. 3 distinct groups with isolated LVA VA were identified: idiopathic (ID), dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) Isolated LV VA accounted for 9/19 (47%) of HCM, 4/566 (0.7%) of DCM and 7/1371 (0.5%) of ID VA ablations. The patient demographics, clinical and characteristic ECG features are summarized in table 1. An example of the VA morphology with LV voltage map and cardiac MRI in an ID case are shown in figure 1. Conclusions: The LVA in the absence of CAD is a rare source of VA. LVA VA has a characteristic ECG morphology, that facilitates localization. The presence of associated LV apical aneurysm is common in those with HCM and DCM. An epicardial origin may be present, with patchy, isolated, apical epicardial scar rarely identified.